Algorithm of generalized coordinates vector evaluation in active damping problem of aircraft elastic oscillations - Синеглазов, В. М.; Онищенко, И. А. (Proceedings of National Aviation University (archive), 1998)
Considered is the evaluation of generalized coordinates vector in the active damping problem of aircraft elastic oscillations. Proposed is the solution of problem based on modal filter synthesis allowing to separate the number of generalized coordinates